FACTORS AFFECTING THE ENTERPRISE PERFORMANCE - Bambang Tjahjadi (Universitas Hayam Wuruk Perbanas, 2011)
Executive leadership has potential role in formulating and executing business strategies to achieve excellence business performance. Any strategy is considered a unique way when cre- ating value. Therefore, it is always changing even though the tools for managing strategies have not yet kept paving the pace. In addition, most companies still focus on financial meas- ures, and their budget in that case remain the center of management control system. Mean- while, in knowledge-based competition, the ability of the organizations to develop, nurture, and mobilize their intangible assets is critical for success. Balanced Scorecard (BSC) has been used as the solution to this performance management and strategy execution problems. This study focused on three competing paths involving four research variables, namely ex- ecutive leadership, business strategy, Balanced Scorecard measures, and performance. This research was based on survey of 127 state-owned enterprises which all have legal form of Persero (per shares) and 408 publicly listed companies in Indonesia Stock Exchange (ISC). However, only 67 companies participated, therefore, the response rate was about 12 percent. The result of this research showed that the hypothesis stating the executive leadership has positive impact on performance through the Balanced Scorecard measures was supported.